2008
DOI: 10.1186/1471-2350-9-106
|View full text |Cite
|
Sign up to set email alerts
|

TCF7L2variant genotypes and type 2 diabetes risk in Brazil: significant association, but not a significant tool for risk stratification in the general population

Abstract: BackgroundGenetic polymorphisms of the TCF7L2 gene are strongly associated with large increments in type 2 diabetes risk in different populations worldwide. In this study, we aimed to confirm the effect of the TCF7L2 polymorphism rs7903146 on diabetes risk in a Brazilian population and to assess the use of this genetic marker in improving diabetes risk prediction in the general population.MethodsWe genotyped the single nucleotide polymorphisms (SNP) rs7903146 of the TCF7L2 gene in 560 patients with known coron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 28 publications
4
19
1
1
Order By: Relevance
“…The odds ratio for the association with genotype TT (recessive model) were 3.92 (CI 95%; 1.49-10.3); and for T allele 1.51 (CI 95%; 1.03-2.21), similar to that reported in the previous study involving the Brazilian population (28), as well as in other populations (10,25,32). The T allele was significantly more frequent in T2D patients than in controls (35.8% versus 27%; p = 0.032).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The odds ratio for the association with genotype TT (recessive model) were 3.92 (CI 95%; 1.49-10.3); and for T allele 1.51 (CI 95%; 1.03-2.21), similar to that reported in the previous study involving the Brazilian population (28), as well as in other populations (10,25,32). The T allele was significantly more frequent in T2D patients than in controls (35.8% versus 27%; p = 0.032).…”
Section: Discussionsupporting
confidence: 76%
“…reported that the T allele of rs7903146 SNP at the TCF7L2 locus is associated with a 1.57 increase in the risk of T2D in a sample of patients with documented multivessel coronary artery disease from the multivessel coronary disease patient studies (MASS II Study) in Southeastern Brazil, although this genetic variant did not increase the accuracy of a validated diabetes risk prediction score for the Brazilian population (28). We have previously shown a 37% frequency of the T allele of rs7903146 SNP at the TCF7L2 locus in a group of 104 healthy young volunteers (mean age of 27.7 ± 11 years) randomly selected in Brasilia, the capital of Brazil (29).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, this polymorphism was found associated with diabetes in several works carried out in admixed populations from other Latin American countries (9,(23)(24)(25)28,29,31,32). However, Barros and cols.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, among Latin American countries there are only reports on the association of TCF7L2 polymorphisms and T2DM from Colombia (23), Brazil (24)(25)(26)(27)(28) and Mexico (9,(29)(30)(31)(32). Latin American populations are characterized by high socioeconomic and genetic heterogeneity with varying degrees of ancestral population proportions from country to country, thus more studies are needed exploring the basis of T2DM susceptibility from these mixed populations.…”
Section: Tcf7l2 Polymorphisms and Type 2 Diabetes Riskmentioning
confidence: 99%
“…Although interventions based on individual genomic risk could potentially lead to adoption of risk reduction behaviors, screening and/or early diagnosis and improved morbidity and mortality, the validity of genomic risk information and likelihood of improving health outcomes is unclear [2][3][4] . Recent data cast doubt on the utility and/or added value of genetic testing [5][6][7][8][9][10][11] . Furthermore, many primary care physicians (PCPs) have limited knowledge of genetic testing or how to translate test results into clinically relevant information [12][13][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%